Pendampingan Manajemen Ide Festival di Sungai Larangan, Desa Wisata Hijau Bilebante, Kecamatan Pringgarata, Kabupaten Lombok Tengah. - Ni Putu Inten Nindya Paramitha; Akhmad Saufi; R. Dimas Bani Adhiman; Ni Nyoman Yunita Aswina Putri; Lani Presia Rabbani (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
The Bilebante Green Tourism Village is one of the tourism villages located in Pringgarata Sub-district, Central Lombok. The Bilebante Green Tourism Village possesses immense natural potential and resources. One of its main attractions or tourism assets is the Larangan River. The Larangan River is an authentic cultural heritage site for the Bilebante Green Tourism Village. However, this potential has not yet been managed optimally due to limited resources and capacity; therefore, there is a need for mentoring or community service aimed at providing a deeper understanding to the community and managers regarding management practices, particularly regarding suitable festival ideas to bring prosperity to the community. The methods used in this mentoring activity include awareness-raising or socialisation sessions, participatory discussions, activity simulations, and mentoring to manage festivals or events on the Larangan River. The outcome of this mentoring activity is that the community is able to draw up a calendar of events/festivals for the tourism village. The community and managers are able to draw up an annual festival calendar that takes various aspects into account, such as the tourist season and environmental conditions. They are also able to draw up and implement Standard Operating Procedures (SOPs). Participants are trained to draw up festival SOPs as operational guidelines for activities